Benign Brenner tumour of the ovary: CT and MRI features. Issue 8 (August 2021) - Montoriol, P.-F.; Hordonneau, C.; Boudinaud, C.; Molnar, I.; Abrial, C.; Kossai, M.
Abstract : AIM: To evaluate the computed tomography (CT) and magnetic resonance imaging (MRI) features of benign Brenner tumours (BBT) of the ovary. MATERIAL AND METHODS: This was a retrospective two-centre study comprising 35 female patients with a definitive diagnosis of BBT at histology in whom CT and/or MRI examinations had been performed. Two experienced radiologists reviewed the CT and MRI features of 39 ovarian BBT retrospectively with consensus reading. The morphological appearance and size of each tumour were recorded. The presence or absence of calcifications within the solid portion was noted at CT. The reviewed characteristics at MRI included qualitative assessment of the signal intensity of the solid portion on diffusion sequence and contrast enhancement, compared to that of the myometrium. RESULTS: CT and MRI images were available for 27 and 28 lesions, respectively. Sixteen patients had both CT and MRI examinations. BBT were unilateral in 89% of patients, and 49% of lesions were solid and 51% were mixed. Calcifications were depicted at CT in 70.4% of lesions. When present, the cystic portion was multilocular in 85% of cases and corresponded to a mucinous lesion in 74% of cases. Enhancement of the solid portion at MRI was inferior or equal to that of the myometrium in 89% of cases and signal on high b - values diffusion images was deemed low or moderate in 93% of cases. CONCLUSION: The combined CT and MRI findings of a unilateral fibrous ovarian mass containing punctate calcifications often associated with a multilocular cyst suggest the diagnosis of ovarian BBT. Highlights: Benign Brenner tumour of the ovary is mostly incidentally discovered. It is frequently associated with mucinous cystadenoma on the same ovary. It usually presents as a unilateral fibrous tumour often containing calcifications.